(x-2)*2=49

Simple and best practice solution for (x-2)*2=49 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-2)*2=49 equation:


Simplifying
(x + -2) * 2 = 49

Reorder the terms:
(-2 + x) * 2 = 49

Reorder the terms for easier multiplication:
2(-2 + x) = 49
(-2 * 2 + x * 2) = 49
(-4 + 2x) = 49

Solving
-4 + 2x = 49

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 2x = 49 + 4

Combine like terms: -4 + 4 = 0
0 + 2x = 49 + 4
2x = 49 + 4

Combine like terms: 49 + 4 = 53
2x = 53

Divide each side by '2'.
x = 26.5

Simplifying
x = 26.5

See similar equations:

| n-3(2)=14-4(2) | | 3v+6=7 | | 41c-41d= | | (a+1)*2=25 | | 7r-4r+5=9r+5-r | | 3x^2+18x+7=0 | | 0=(6-7x)10 | | (x-2)(y+3)=35 | | 2y+x=23 | | 5j-25=35 | | f(x)=x^4+x^3+x^2-9x-10 | | 8x-5=2x-5 | | 3-386+2= | | 4y+1y=13 | | x+1x+9=23 | | .38=2b+25*(-7) | | 17x^17=0 | | (Y-3)(Y^2+BY+C)=Y^3-27 | | 19(3-v)+10v=-15 | | -4(6x-7)-3(4+2x)= | | 3x+45=3(x-3) | | 6X(2x-1)= | | 3(2x-y)+6y= | | 0.3(y+4)=0.4(y-2) | | 19=35+9x | | 2(-1)-4-y=12 | | 3y-(y+2x)+x= | | 6y-9-3y+8=0 | | 2(0)-4-y=12 | | 4y-5x=4 | | 2(1)-4-y=12 | | 2z-18-4z=-9 |

Equations solver categories